PENDUGAAN UMUR SIMPAN PRODUK BISKUIT DENGAN METODE AKSELERASI BERDASARKAN PENDEKATAN KADAR AIR KRITIS [Accelerated Shelf-life Testing of Biscuits Using a Critical Moisture Content Approach] - Feri Kusnandar; Dede R. Adawiyah; Mona Fitria (Jurnal Teknologi dan Industri Pangan, 2010)
The objective of this research was to determine the shelf-life of commercial soft and hard dough biscuits packed in metallized plastics by using a critical moisture content approach. The critical moisture contents, which were reached when the biscuits started to loss their crispiness and firmness, were 0,064 g H2O/g dried solid for soft dough biscuit and 0.069 g H2O/g dried solid for hard dough biscuit. The soft dough biscuits stored at 30oC and relative humidity of 75% had shelf life of 17.4 months, while that of hard dough biscuit at the same storage condition had shelf life of 16.5 months.